Workload and professional competence as a correlate of mathematics teachers’ teaching effectiveness in secondary schools in Osun State, Nigeria (2019)
This study is hinged on the balancing of the workload and professional competence of mathematics teachers in secondary schools in Osun State, Nigeria which was premised on cognitive load theory. The study adopted the descriptive survey design. One hundred and nineteen mathematics teachers were randomly selected from both public and private secondary schools in 10 local government areas of Osun State. Instruments used were Workload Scale (r=0.78), Professional Competence Scale (r=0.83) and Teaching Effectiveness Scale (r=0.87). Data were analysed using descriptive statistics of frequency count, percentage, mean, while Pearson product moment correlation, t-test and Analysis of variance were used for analyzing the data at 0.05 level of significance. Professional competence (r=0.39) and workload (r=0.26) had positive significant relationship with mathematics teachers' teaching effectiveness. Mathematics teachers' teaching effectiveness in terms of methodology, curriculum and textbook usage, knowledge of their students, context and self were high as against the threshold of 3.0 as the criterion point. Among other things, it was recommended that there should be re- evaluation of the professional training of Mathematics teachers regardless of where they work.